THE ABILITY OFTHE STUDENTS OF CLASS X DEPARTMENT OFFICE ADMINISTRATION IN DRAWING PENCIL COLOR WITH MEDIA ILLUSTRATION IN SMK NEGERI 2 BELOPA - Andi Hasan Basri; Benny Subiantoro; Tangsi Tangsi (Universitas Negeri makassar, 2019)
This study aims to describe: (1) The ability of X class students Department of Administration Office SMK Negeri 2 Belopa in Drawing Illustration with color pencil media. (2) Obstacles encountered in the process of Drawing Illustration with colored pencil media in the class X student Department of Administrative Office at SMK Negeri 2 Belopa. This research is included in the type of evaluative research on the qualitative level, with data collection techniques such as observation, test, and documentation. The subjects of this study are the students of class X of the Department of Administration Office at SMK Negeri 2 Belopa amounted to 24 people. The results of this study indicate that: (1) Drawing Ability Illustration with color pencil media at grade X students Department of Administration Office at SMK Negeri 2 Belopa less, that is average value 58. Based on Standard Minimum Exhaustiveness Criteria (KKM), hence the result of the ability above has not reached, the established KKM is 70. While the result of the ability of Illustration Drawing with colored pencil media is only 58. (2) Constraints faced by students, namely the lack of attention of students in following the learning and interest of students in the lesson of art and culture, principles of drawing, and lack of mastery of students in the aspect of mastery of technique/media.